Emotional aging: a discrete emotions perspective - Kunzmann, Ute; Kappes, Cathleen; Wrosch, Carsten (Frontiers in Psychology, 2014)
Perhaps the most important single finding in the field of emotional aging has been that the overall quality of affective experience steadily improves during adulthood and can be maintained into old age. Recent lifespan developmental theories have provided motivation- and experience-based explanations for this phenomenon. These theories suggest that, as individuals grow older, they become increasingly motivated and able to regulate their emotions, which could result in reduced negativity and enhanced positivity. The objective of this paper is to expand existing theories and empirical research on emotional aging by presenting a discrete emotions perspective. To illustrate the usefulness of this approach, we focus on a discussion of the literature examining age differences in anger and sadness. These two negative emotions have been subsumed under the singular concept of negative affect. From a discrete emotions perspective, however, they are highly distinct. Sadness is elicited by an irreversible loss and associated with low situational control, high goal adjustment tendencies, and the motivation to search for social support. The experience of anger, by contrast, is typically triggered by other individuals who intentio